A case study of brownfield redevelopment in Wellston, MO - Williams, Ashley (Kansas State University, 2009)
This report reviews pertinent knowledge regarding brownfield redevelopment, specifically the processes and issues involved. It addresses such topics as the type of brownfield sites, steps to remediation, types of remediation and barriers to redevelopment. Finally, a precedent study of Wellston, MO is presented. This study examines the impact that the development of two abandoned brownfield sites, Wellston Electrical Company and ABEX Foundry, had on the entire community. It was found that the onset of the development of these sites spurred the revitalization of the whole city of Wellston, having a positive influence across the city and surrounding area.
Keywords: Brownfield; Redevelopment; Wellston, MO; Infill; Architecture (0729); Urban and Regional Planning (0999)